Interactive Pictorial Story as Learning Media for Third Grade Students - Nurul Inayah; Andarini Permata Cahyaningtyas; Rida Fironika Kusumadewi (Universitas Muhammadiyah Surakarta, 2021)
This study aims to develop an interactive pictorial story as a learning media on theme 2 Loving Plants and Animals and to determine its feasibility, practicality, and effectiveness. This study uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In this study, the results obtained include: (1) The feasibility of the media obtained from the validation results by 5 validators obtained an average of 0.83 for content quality indicators and objectives, instructional quality indicators obtained an average of 0.84 and technical quality indicators obtained an average of 0.83. The average number of all indicators is 0.83 with the category